2008
DOI: 10.1002/mrm.21461
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and MR spectroscopy in hypertension and presumed cerebral small vessel disease

Abstract: In patients with cerebral small vessel disease (SVD) diffusion tensor imaging (DTI) is sensitive to white matter damage and correlates better with cognitive function than conventional imaging. It has been proposed as a surrogate marker for treatment trials. However, the pathological changes underlying DTI are not known. The purpose of this study was to use magnetic resonance spectroscopy (MRS) to determine the pathological changes underlying DTI abnormalities in a range of patients from asymptomatic white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
5
54
1
3
Order By: Relevance
“…The increase in PPL mI/Cr in our series agrees with a previous report showing higher mI/Cr values in the peritrigonal white matter of patients with asymptomatic hypertension. 5 Regarding the changes in frontal NAA/Cr ratio, the ratio drop in our resistant hypertensive patients is in agreement with two recent chemical-shift imaging reports involving the white matter of the centrum semiovale 21 and particular areas in the white and gray matters. 22 These studies showed decreasing NAA concentrations associated with increasing severity of disease 21 and NAA/Cr decreases in the gray matter of hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in PPL mI/Cr in our series agrees with a previous report showing higher mI/Cr values in the peritrigonal white matter of patients with asymptomatic hypertension. 5 Regarding the changes in frontal NAA/Cr ratio, the ratio drop in our resistant hypertensive patients is in agreement with two recent chemical-shift imaging reports involving the white matter of the centrum semiovale 21 and particular areas in the white and gray matters. 22 These studies showed decreasing NAA concentrations associated with increasing severity of disease 21 and NAA/Cr decreases in the gray matter of hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…5 Regarding the changes in frontal NAA/Cr ratio, the ratio drop in our resistant hypertensive patients is in agreement with two recent chemical-shift imaging reports involving the white matter of the centrum semiovale 21 and particular areas in the white and gray matters. 22 These studies showed decreasing NAA concentrations associated with increasing severity of disease 21 and NAA/Cr decreases in the gray matter of hypertensive patients. 22 Contrary to these results, NAA/Cr was not found to differ between treated and untreated hypertensive patients in a recent related study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ischemic changes in the white matter can be seen by either 1 H-MRS or DTI and the results are comparable. 91 Diffusion tensor imaging allows measurements of fractional anisotropy and mean diffusivity. 92 Quantification of DTI may be confounded by the heterogeneity of white-matter regions with crossing fiber tracts, which can often be overcome with appropriate image processing methods.…”
Section: Nmr Spectroscopy and Diffusion Tensor Imagingmentioning
confidence: 99%